Processo decisório e estratégia : um estudo de múltiplos casos em empresas de serviços intensivos em conhecimento (SICs) na cidade de Aracaju-SE - Silva, Jalberto Dória da (2014)
Decision-making process is an inherent daily life and business element. Its relevance to administration is such that, for some authors, to make a decision is a synonym of managing (MAXIMIANO, 2011). At the strategic level, these decisions are made by the senior managers of the organization and are related to the execution of the critical activities. This study used the strategy as a social practice approach in the analysis of decision making. By this perspective, the strategy is defined as the way by which the managers and others involved in an organization interact and operate throughout the whole process of formulating and implementing the strategy, focusing on the social practices of everyday life (AVILA et al., 2009). On this study, the background considered in the strategic decision-making process are the organizations of knowledge intensive business (KIBs), characterized by Miles et al. (1995) as companies that rely heavily on professional knowledge, are primary sources of information and knowledge, use their knowledge to produce intermediary production processes of its customers, have great competitive importance and are the main providers of other enterprises. Thus, it was defined as the research objective of this investigation the analysis of how the strategic decision-making process takes place in SICs of Aracaju-SE. To achieve this purpose, a methodological qualitative approach was proposed. The research strategy of multiple cases was adopted in order to describe and, at the same time, to explore the studied phenomenon. Nevertheless, the triangulation of data was developed through the collection on primary sources, conducting interviews and observation, and secondary sources, documental analysis. On the investigated cases, it was observed that companies were unincorporated, and relied on very lean and highly qualified teams. It is noteworthy that the strategic goals and the objectives of the organizations are well defined and disseminated among their peers. Members participate actively on the meetings, but the most crucial issues are concentrated on partners and certain key employees. These actions impact directly on the decision-making, since they are taken together in regular meetings with the participation of all staff and, in some cases, of customers and suppliers. As a consequence, the preponderant influence of external factors – such as customers, suppliers, competitors and technology – is assumed on the decision-making process of these companies. It was also observed the use of analytical methods and software to support the decision-making. Such considerations on how the strategic decision is taken in these organizations reflect the notion of strategy as social practice. This can be observed by the three concepts of the theory: Practitioners of the strategy; social, symbolic and material Practices through which the strategy is carried out and the Praxis or flow of activity in which the strategy is developed.